Analisis Sistem Insentif Jasa Pelayanan Dalam Meningkatkan Kinerja Pegawai Di RSUD Pandega Pangandaran - Taufik Hermanto; Apri Budianto; Aini Kusniawati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The incentive system at Pandega Pangandaran Regional Hospital is not optimal in terms of proportionality, that is, there are quite significant differences in the receipt of incentives for nursing staff for the same item and in the same month. Apart from that, employee performance is not yet optimal in terms of work quality, namely there is still a lot of work that is not completed on time, employee attitudes are less friendly towards visitors, and employees are not quick and agile in serving patient wishes. Furthermore, working time is not optimal because there are still complaints, especially doctors' hours which are sometimes not on time and nurses have not been able to make good use of working time so that their work is not fulfilled according to the schedule set by the hospital. The research was conducted using a descriptive analysis method with a qualitative design. The data analysis techniques used are Data Reduction, Data Presentation, Conclusion Drawing, and Triangulation. The results of the research show that (1) The service incentive system at Pandega Pangandaran Regional Hospital is not optimal, this is because the indicators in the service incentive system are not running optimally, namely proportionality, but the indicators of performance, professionalism, distributiveness and teamwork are running optimally. (2) The performance of employees at Pandega Pangandaran Regional Hospital is not yet optimal, this is because the performance indicators have not been optimal, namely the quality produced and working time, but the quantity produced and cooperation has run optimally. (3) The service incentive system can improve employee performance at Pandega Pangandaran Regional Hospital. This means that the better the service incentive system, the higher the employee performance at Pandega Pangandaran Regional Hospital.